Intellectual property valuation and innovation : towards global harmonisation - Taplin, Ruth (Routledge studies in the growth economies of Asia ;, 2014)
"Intellectual property is an increasingly key element in business worldwide. Methods for valuing intellectual property however vary widely. Moreover, issues surrounding the ownership and valuation of intellectual property give rise to a wide range of ethical issues, which apply especially in developing countries as they are increasingly integrated into the world economy. International agreement on how intellectual property should be valued is urgently needed. This book provides an overview of the issues surrounding the valuation of intellectual property, and assesses the steps being made towards harmonization"--